2012
DOI: 10.1016/j.ijcard.2011.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure is associated with subclinical atherosclerosis in spinal cord injury subjects

Abstract: Subjects with chronic spinal cord injury (SCI) exhibit increased subclinical atherosclerosis and worse left ventricular diastolic function in comparison to able-bodied individuals, independent of traditional cardiovascular risk factors [1][2][3][4]. SCI may impair the descending spinal sympathetic tract and promote alterations in blood pressure (BP) profile, such as loss of nocturnal dipping due to orthostatic hypotension, and labile hypertension secondary to uncontrolled sympathetic output as a consequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…From the ABPM data we found that only one of the 42 subjects had daytime hypertension, while 33% had nocturnal hypertension. Half our population had night-time pressures higher than daytime pressures; this is in keeping with previous studies that compared diurnal BP between paraplegia, tetraplegia and able-bodied controls, and observed that in people with high-level SCI (above T6), the day BP was lower compared to low-level injury and controls, whilst no differences were noticed in night BP [22][23][24][25][26][27][28][29]. Therefore, the pathology of OSA and non-dipping status in the SCI population presumably relates to lower daytime, but preserved night-time BP, while in the ablebodied populations surges in night-time sympathetic activity during an apnoeic/hypopnoeic event contributes to nondipping status.…”
Section: Bp Pattern Vs Osasupporting
confidence: 89%
“…From the ABPM data we found that only one of the 42 subjects had daytime hypertension, while 33% had nocturnal hypertension. Half our population had night-time pressures higher than daytime pressures; this is in keeping with previous studies that compared diurnal BP between paraplegia, tetraplegia and able-bodied controls, and observed that in people with high-level SCI (above T6), the day BP was lower compared to low-level injury and controls, whilst no differences were noticed in night BP [22][23][24][25][26][27][28][29]. Therefore, the pathology of OSA and non-dipping status in the SCI population presumably relates to lower daytime, but preserved night-time BP, while in the ablebodied populations surges in night-time sympathetic activity during an apnoeic/hypopnoeic event contributes to nondipping status.…”
Section: Bp Pattern Vs Osasupporting
confidence: 89%
“…SCI subjects might present asymptomatic heart diseases, coronary, for instance, arrhythmias, autonomic dysreflexia, and increased blood pressure taking into account the lack of access to appropriate exercise . They present thicker carotid intima‐media as measured by echocardiography, exhibiting vascular and inflammatory surrogates with cardiovascular risk, although subclinical carotid atherosclerosis relates to lesion level and not to increased inflammatory condition .…”
Section: Functional Diagnoses and Therapymentioning
confidence: 99%
“…These can be troublesome in terms of quality of life, leading to feelings of fatigue [2], decreased participation in activities of daily living and rehabilitation [3] and impaired cognitive function [4]. While blood pressure (BP) and heart rate (HR) have been studied in adults with SCI [5][6][7], there are few studies assessing normative values in the pediatric SCI population (0-18 years old) [8,9]. In addition, there have been no studies to date that have examined these parameters in adolescents and young adults (16-21 years old), yet this is the most prominent age range for the onset of SCI in both males and females [10].…”
Section: Introductionmentioning
confidence: 99%
“…These include, reduced observer bias and device inaccuracies (digit preference), capture of wide fluctuations in BP and limitations of the "white coat effect" [11,12]. Although many studies [4,6,7,13] have used ABPM to investigate daily fluctuations in BP and HR in adults with SCI, there are currently no reports of its usage in the youth and adolescent SCI population. Several studies have provided evidence that ABPM can be performed with success in the non-SCI population among individuals with different age ranges (infants to late teenagers) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%